A novel mechanism of conjugate formation of bisphenol A and its analogues by Bacillus amyloliquefaciens: Detoxification and reduction of estrogenicity of bisphenols. (April 2016) - Zühlke, Marie-Katherin; Schlüter, Rabea; Henning, Ann-Kristin; Lipka, Marko; Mikolasch, Annett; Schumann, Peter; Giersberg, Martin; Kunze, Gotthard; Schauer, Frieder
Abstract: A bacterial strain with the ability to transform bisphenol A (BPA) and other so-called "new-generation bisphenols" like bisphenol C (BPC), bisphenol E (BPE), bisphenol F (BPF) and bisphenol Z (BPZ) was isolated from sewage sludge and identified as Bacillus amyloliquefaciens . We investigated the biotransformation of bisphenols and analyzed the toxicity and estrogenicity of the products formed compared to the parent compounds. During the incubation of this bacterial strain with different bisphenols one major metabolite was detected in each case by HPLC but its formation was partly reversible. Highest transformation rate of 77% of the initial concentration applied was determined for BPA and BPE. Mass spectrometric and nuclear magnetic resonance spectroscopic analyses as well as deconjugation experiments proofed the formation of phosphate conjugates with each bisphenol. The conjugates formed were considerably less toxic and less estrogenically active than their parent bisphenols. Highlights: Bacillus amyloliquefaciens was isolated from sewage sludge. The bacterium transforms bisphenols to phosphate conjugates. Phosphate conjugation of bisphenol A and related bisphenols is partly reversible. Estrogenicity and toxicity of bisphenols depend on structure. Phosphate conjugates are non-toxic and less estrogenically active than bisphenols.